SNAP-tag2 for faster and brighter protein labeling - Kühn, Stefanie; Nasufović, Veselin; Wilhelm, Jonas; Kompa, Julian; de Lange, Eline M. F.; Lin, Yin-Hsi; Egoldt, Cornelia; Fischer, Jonas; Lennoi, Artem; Tarnawski, Miroslaw; Reinstein, Jochen; Vlijm, Rifka; et al. (Nature chemical biology, 2025)
SNAP-tag is a powerful tool for labeling proteins with synthetic fluorophores in bioimaging. However, its utility in live-cell applications can be constrained by its relatively slow labeling kinetics and the limited cell permeability of its substrates. Here, we introduce improved labeling substrates and an engineered SNAP-tag for faster labeling in vitro and in live cells. SNAP-tag2 presents a second-order rate constant with rhodamine substrates that approaches 107 s−1 M−1, a 100-fold improvement over the corresponding SNAP-tag-substrate pairs. When labeled with highly fluorogenic dyes, SNAP-tag2 also shows a fivefold increase in fluorescence brightness relative to currently used SNAP-tag. The increased labeling kinetics and brightness of SNAP-tag2 translate into greatly improved performance in various live-cell (super-resolution) imaging applications.
Gesehen am 18.11.2025